(3GdehGRfGJ GdTQYjI Hjf abg GdfU habg GdhGbY (B/ s - (3CHh HcQ eMeO eMehO GdWQGHjdjs; (3YHOGdYRjR QeVGf Sec (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2018)
(3GdYbd GdESdGei GdPi HfGg GdhMi gh Ybd GSJbQGFj GSJfJGLj HQgGfi JYqdei h JMdjdi(B: (3Ybd jMbb GdJMhd ef YbdjI GdJdbjf h GdJdbi Edi YbdjI GdJacjQ h GdGSJfJGL h GdGSJOdGd h GdGSJbQGA h GdJMdjd h GdfbO h GdehGRfI h GdGSJTQGa GdeSJbHdi h YOe GdbHhd HCi acQ Ch GLJgGO HZjQ SdWGf Ch HZjQ HQgGf JMJ TYGQ (B((3gGJhG HQgGfce(B): (3h jeJdc COhGJ GdHMK h GdeYQaI h EecGfjI GdfXQ ai GdeBdGJ h GdYhGbH(B: (3agh Ybd jMSf GdJYGed eY GdCSHGH h GdebOeGJ h JSNjQ GdSff(B: (3h jeJdc fGUjI SfI GdeOGaYI(B: (3ajSJWjY eOGaYI bOQ HbOQ CMH Edi Gddg(B. (3agh Ybd jbjS ebGUOg(B: (3jOQc Cf Gddg de jNdbfG YHKG(B: (3adG ecGf ai GdYbd GdeSde ddeUGOaI h GdYThGFjI h GdNhGQbjI ai gPG GdhLhO Gdchfi(B: (3h dG eLGd dGfJaGA GdCSHGH(B. (3h GdYbd GdeSde HgPg GdUhQI gh GdPi jJYGed eY GdebGUO GdTQYjI h jQHWgG HGdhGbY(B: (3aebGUO GdTQjYI GdESdGejI gi GdVhA GdPi jMOO dfG cja fJYGed eY GdhGbY(B: (3Hd gi GdVGHW GdChd GdPi jVHW YdGbI GdhGbY HGdCMcGe GdTQYjIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, (B2018.s
(3HHdjhLQGajG(B: (3UaMGJ (B-299: 312.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3ebGUO GdTQjYI GdESdGejIs; (3MLjI GdGLJgGO GdebGUOjs; (3abg GdhGbYs; (3GdbVGA Hjf abg GdfU habg GdhGbYs; (3YbO GdEeGeIs; (3abg GdCbdjeGJ GdeSdeIs; (3GdMce GdTQYj aj GdgfOSI GdhQGKjIs; (3Hfc GdMjhGfGJ GdefhjIs; (3ebGUO GdTQjYI GdESdGejIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2018